2015
DOI: 10.1016/j.crme.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A robust and well-balanced numerical model for solving the two-layer shallow water equations over uneven topography

Abstract: Available online xxxxKeywords: Two-layer system Well-balanced model Nonconservative 2LSWE HLL A robust and well-balanced numerical model is developed for solving the two-layer shallow water equations based on the approximate Riemann solver in the framework of finitevolume methods. The HLL (Harten, Lax, and van Leer) solver is employed to calculate the numerical fluxes. The numerical balance between the flux gradient and the source terms is achieved by using a balance-reformulation method. To obtain exactly the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…To purify the problem, as was done in previous relevant studies (e.g., Lee et al [9]; Swartenbroekx et al [20]; Hu et al [21]), the flows in the layers are assumed to be immiscible and have constant densities in each layer. Following Lu et al [11], we consider solving the following 2LSWEs system:…”
Section: Governing Equations and 2lhrmmentioning
confidence: 99%
See 1 more Smart Citation
“…To purify the problem, as was done in previous relevant studies (e.g., Lee et al [9]; Swartenbroekx et al [20]; Hu et al [21]), the flows in the layers are assumed to be immiscible and have constant densities in each layer. Following Lu et al [11], we consider solving the following 2LSWEs system:…”
Section: Governing Equations and 2lhrmmentioning
confidence: 99%
“…This method is able to numerically maintain quiescent flow at rest, yet it violates the principle of mass conservation because the temporal variation of the interface is unconsidered. An alternative ad-hoc technique 2 Mathematical Problems in Engineering was proposed by Lu et al [11], by limiting the diffusion part of numerical fluxes so that a zero mass flux is predicted under a QFC. To achieve high-resolution numerical solutions, Abgrall and Karni [12] added two auxiliary equations to the conventional 2LSWEs with a relaxation parameter; their numerical results showed that this method generally works well, but spurious oscillation may occur when an inappropriate relaxation parameter is chosen and the predictions may be grid-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…wherẽ− 1/2 is calculated by (17); the minimum is defined over the whole simulation domain. Note that, for this particular test, is commonly set to be a large value (e.g., ≈ 0.5) in literatures [8] and thus the numerical diffusion in the predictions is insignificant.…”
Section: Numerical Test For the 1lswesmentioning
confidence: 99%
“…− ℎ 1 ( ℎ 2 / ) in (24) is a nonconservative product term, which has no definition around shocks and discontinuities and is tough to process in numerical discretizations. Following Spinewine et al [18], and Lu et al [17], the 2LSWEs are reformulated to make the nonconservative product term vanish. This is done by replacing the equations governing the lower-layer flow motions by a combination of the equations for the two-layer flow system as a whole; namely, the 2LSWEs are recast to (10) with vectors defined by…”
Section: Governing Equations and Numericalmentioning
confidence: 99%
See 1 more Smart Citation